Relevansi Konsep Hutan Wakaf dengan Konsep Wakaf di dalam Islam - Devid Frastiawan Amir Sup Devid (Faculty of Economics and Management, 2021)
This study aims to find the relevance of the concept of waqf forest with the concept of waqf in Islam. The method used is qualitative-literature-descriptive. The conclusion obtained, waqf is holding ownership of one's property so that the benefits can be distributed for the benefit of the people, both in terms of social, economic, scientific, and so on including the environment. Waqf forest is a form of productive waqf in rebuilding a land to be used as a forest. The benefits of waqf forests can be used for social benefits, namely as a source of oxygen, springs, and life for many creatures. In the economic field, waqf forests can produce economic goods, waqf forests can also be used by local residents (provided they are not allowed to damage the forest), and there are many other benefits of waqf forests. Based on the meaning, pillars, conditions, and objectives of waqf, the waqf forest has relevance to the concept of waqf in Islam. In addition, waqf forests are also in accordance with the provisions in waqf regulations in Indonesia as stated by BWI.